EVALUACIÓN DE LA CAPACIDAD PROBIÓTICA “IN VITRO” DE UNA CEPA NATIVA DE Saccharomyces cerevisiae - Ángela Ortiz; Joanna Reuto; Erika Fajardo; Sandra Sarmiento; Andrea Aguirre; Gustavo Arbeláez; David Gómez; Balkys Quevedo-Hidalgo (Universitas Scientiarum)
The in vitro probiotic capacity of a native strain of Saccharomyces cerevisiae (A) was evaluated and comparedwith a commercial strain (B) used as a probiotic. The effect of the concentration of sugarcane molasses (10, 20and 30% (w/v)) on the biomass production was investigated and kinetic parameters were determined. The bestmolasses concentration was 20% (w/v) and differences in biomass production on molasses medium betweenstrain A (28 g/L) and control strain B (3 g/L) were observed. In vitro tests such as tolerance to bile salts, pH andgastric juices were carried out, and no differences in growth between strain A and B were found. Cholesterolreduction on presence of bile salts after 12 hours of incubation was of 54% for strain A and 58% for strain B.Both strains showed adherence to Caco-2 cells. Results reveal that strain A possesses in vitro probiotic propertiesthat can be verified with further in vivo studies to confirm its suitability as probiotic in animal nutrition.